Inclusive Education as a Path to Liberation : An Observational Study at School of Universe Bogor - Widya Rahmawati Al-Nur; Samsul Nurhidayat; M Alghiffari P; Nur Azizah Rahmani; Siti Aisyah (BASICA, 2025)
Inclusive education is one of the alternatives to equitable distribution of education in Indonesia. Inclusive education also provides opportunities for students to be equal in their rights to education and socialization for inclusion students more freely. This study aims to analyze the implementation of inclusive education at the School of Universe (SOU), Parung, Bogor. The research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that SOU, a nature school, has been implementing inclusive education since its inception. The curriculum at SOU is adapted through duplication and modification strategies to meet the diverse learning needs of students, and trained co-teachers are involved in learning and extracurricular activities to support students with special needs. Inclusive evaluations at SOU are conducted periodically with a special assessment format to monitor the progress of each student. The research also identified the main challenges in the form of limited learning facilities and the capacity of available support staff. Nonetheless, the findings show that inclusion practices at SOU reflect the school's strong commitment to equitable inclusion education, where every student gets the opportunity to learn as they need.